KOMODITAS POTENSIAL TANAMAN PALAWIJA DI KABUPATEN BLORA PROVINSI JAWA TENGAH - Agus Yuniawan Isyanto; Sudrajat Sudrajat; Muhamad Nurdin Yusuf; Ane Novianty; Beniidzar M. Andrie; Wulan Priantika; Nurlina Harli; Saepul Aziz (Universitas Galuh Ciamis, 2019)
Identification of potential commodities needs to be done in the context of the economic development of a region. This research was carried out with the aim of identifying potential commodities of secondary crops in Blora District, Central Java Province. Data analysis was carried out using the Location Quotient (LQ) method. The results showed that corn was a base commodity for Randublatung, Kradenan, Sambong, Jiken, Bogorejo, Jepon, Banjarejo, and Tunjungan Subdistricts and Blora City. Soybean is a base commodity for Jati, Kedungtuban, Japah and Kunduran Subdistricts. Peanuts are the base commodity for Kedungtuban, Cepu, Japah and Todanan Subdistricts. Mung beans are a basic commodity for Jati, Cepu, Sambong, Japah, Ngawen and Kunduran Subdistricts. Sweet potato is a base commodity for Kradenan, Sambong, Tunjungan and Ngawen Subdistricts, and Blora City. Cassava is a commodity base for the Kradenan, Sambong, Jiken, Banjarejo, Japah and Ngawen Districts